Engineering cases and deviatoric stress distributions under trapezoidal load in coal pillar floor - Lan Shizhong; Xie Shengrong; Suo Haixiang; Zhang Tao (矿业科学学报, 2019)
A mechanical model of the deviatoric stress distribution of the floor under the trapezoidal load was established,and the maximum principal stress formula of the floor under coal pillar was derived,and the response characteristics of the deviatoric stress field of the floor under the different load spans and the asymmetry coefficient were obtained.With the decrease of the load spans,the deviatoric stress value of the floor was decreased,and the degree of asymmetry of the high deviatoric stress concentration area in the two sides of the floor was weakened,and eventually there was convergencing to form a continuous high deviatoric stress area shaped like “apple”.When 1<λ≤4,the distribution is asymmetry saddle type consistent with the load level.With the increase of λ value,the asymmetry was increased,and the growth rate of the high load side was significantly higher than that of the low load side.The minimum value increased linearly,and its position is shifted to the low load side.When the load span was 35 m,with the increase of depth,the asymmetric trend of the deviatoric stress became slow,while there was a relatively obvious low deviatoric stress area in a certain range of the floor,which could be used as the ideal area of roadway layout.Combined with the geological conditions and mechanical analysis of Xinyang coal mine,the Xin No 102 material roadway was arranged at x=15 m,and the supporting scheme of the high prestress and intensive bolt (cable) was determined.We carried out the field tests and achieved good control effects.These provide theoretical basis and technical reference for the roadway layout and control of surrounding rock in the lower seam of close distance coal seams.